Death spiral PIPEs: a reconsideration of the evidence. (10th September 2019) - Benson, Karen; Linnenluecke, Martina K.; Morrison, David; Rosov, Sviatoslav
Abstract: We challenge the view that PIPEs lead to unfavourable outcomes for issuing firms. We show that structured PIPEs do not have significant negative CARs when a matched firm benchmark is used for computing CARs and when sample selection bias is taken into account. Indeed, structured PIPEs have significantly higher positive skewness, indicating superior optionality, consistent with the real option argument. We also show that the 2002 intervention by the Securities and Exchange Corporation (SEC) has led to unintended consequences, with the substitution of 'mom and pop' investors for hedge fund investors in the structured PIPE market.